2013
DOI: 10.1002/smll.201300607
|View full text |Cite
|
Sign up to set email alerts
|

Multiwall Carbon Nanotubes Mediate Macrophage Activation and Promote Pulmonary Fibrosis Through TGF‐β/Smad Signaling Pathway

Abstract: Multiwall carbon nanotubes (MWCNTs) have been widely used in many disciplines due to their unique physical and chemical properties, but have also raised great concerns about their possible negative health impacts, especially through occupational exposure. Although recent studies have demonstrated that MWCNTs induce granuloma formation and/or fibrotic responses in the lungs of rats or mice, their cellular and molecular mechanisms remain largely unaddressed. Here, it is reported that the TGF-β/Smad signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
142
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(146 citation statements)
references
References 45 publications
2
142
0
2
Order By: Relevance
“…Biopersistent nanofibers with stiff nanostructures can induce significant inflammation, fibrosis or granuloma when these nanostructures are too long to be phagocytized by macrophages. Carbon nanotubes (CNTs) as the most well-known HAR nanomaterial can trigger pulmonary toxicity due to fibrosis, which is mainly caused by macrophage activation, TGF-b induction and enhanced collagen deposition [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Biopersistent nanofibers with stiff nanostructures can induce significant inflammation, fibrosis or granuloma when these nanostructures are too long to be phagocytized by macrophages. Carbon nanotubes (CNTs) as the most well-known HAR nanomaterial can trigger pulmonary toxicity due to fibrosis, which is mainly caused by macrophage activation, TGF-b induction and enhanced collagen deposition [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nanosafety studies depend on scientific reports on the biological effects of nanoparticles (NPs) in living organisms, in order to predict and correct the possible deleterious impact on human and environmental health. Many studies showed that NPs may have adverse effects on health, mainly due to their small size, large surface area per mass and highly reactive properties (Bast us et al 2008;Ge et al 2012;Li et al 2012;Wang et al 2013). Among the different NP effects in biological systems, activation of immune responses is considered a central element for assessing health risks of NPs (Boraschi and Duschl 2012;).…”
Section: Introductionmentioning
confidence: 99%
“…16 The transforming growth factor-beta (TGF-β) signaling cascade has been elaborated to be involved in CNTinduced pulmonary inflammation, epithelial-to-mesenchymal transition (EMT), and fibrogenesis. [17][18][19][20][21] Biomedical applications such as delivery of therapeutic agents and imaging diagnosis based on CNTs are carried out mainly via intravenous or subcutaneous routes. Hence, the biocompatibility and safety of CNTs introduced directly into the bloodstream or other biologic tissue should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…18 Subsequently, the phosphorylated Smad2 heterodimerizes with Smad4 to form Smad2/4 complexes that translocate to the nucleus and bind to the promoter regions of pro-fibrotic genes such as collagen and α-SMA.…”
mentioning
confidence: 99%